Synthesis of Pd/Ru Bimetallic Nanoparticles by Escherichia coli and Potential as a Catalyst for Upgrading 5-Hydroxymethyl Furfural Into Liquid Fuel Precursors - Gomez-Bolivar, Jaime; Mikheenko, Iryna P.; Orozco, Rafael L.; Sharma, Surbhi; Banerjee, Dipanjan; Walker, Marc; Hand, Rachel A.; Merroun, Mohamed L.; Macaskie, Lynne E. (Frontiers in Microbiology, 2019)
Escherichia coli cells support the nucleation and growth of ruthenium and ruthenium-palladium nanoparticles (Bio-Ru and Bio-Pd/Ru NPs). We report a method for the synthesis of these monometallic and bimetallic NPs and their application in the catalytic upgrading of 5-hydroxymethyl furfural (5-HMF) to 2,5 dimethylfuran (DMF). Examination using high resolution transmission electron microscopy with energy dispersive X-ray microanalysis (EDX) and high angle annular dark field (HAADF) showed Ru NPs located mainly at the cell surface using Ru(III) alone but small intracellular Ru-NPs (size ~ 1-2 nm) were visible only in cells that had been pre-‘seeded’ with Pd(0) (5 wt%) and loaded with equimolar Ru. Pd(0) NPs were distributed between the cytoplasm and cell surface. Cells bearing 5%Pd/5%Ru showed some co-localization of Pd and Ru but chance associations were not ruled out. Cells loaded to 5 wt% Pd/20wt% Ru showed evidence of core-shell structures (Ru core, Pd shell) at the cell surface. Examination of the cell surface material using X-ray photoelectron spectroscopy (XPS) showed Pd(0) and Pd(II) and Ru(IV) and Ru(III), with confirmation by XANES and EXAFS analysis of bulk material. Both Bio-Ru NPs and Bio-Pd/Ru NPs were active in the conversion of 5-HMF into 2,5-DMF but commercial Ru on carbon catalyst outperformed 5 wt% bio-Ru by 4-fold. While 5wt%Pd/20wt%Ru achieved 20% yield of DMF the performance of the 5wt%Pd/5wt%Ru bio-catalyst was higher and comparable to the commercial 5wt% Ru/C catalyst in a test reaction using commercial 5-HMF (> 50% selectivity). 5-HMF was prepared by thermochemical hydrolysis of starch and cellulose with solvent extraction of 5-HMF into methyltetrahydrofuran (MTHF). Under these conditions and with MTHF as the reaction solvent the commercial Ru/C catalyst had little activity (100 conversion, negligible selectivity to DMF) whereas the 5wt%Pd/5wt%Ru bio-bimetallic gave 100% conversion and 14% selectivity to DMF from material extracted the hydrolyzates. The results indicate a potential green method for realising increased energy potential from biomass wastes as well as showing a novel bio-based pathway to manufacturing a scarcely-described bimetallic material.